PENGARUH PENGETAHUAN DAN PERSEPSI BAGI HASIL TERHADAP MINAT MENJADI NASABAH DI BANK SYARIAH : (Studi kasus di Desa Bukit Tigo Kecamatan Singkut Kabupaten Sarolangun) - Amirul Mukminin; Ahmad Syahrizal; Victor Diwantara (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the influence of knowledge and perception of profit sharing on interest in becoming a customer at a Sharia Bank in the community of Bukit Tigo Village, Singkut District, Sarolangun Regency. This research used a quantitative approach which was carried out by distributing questionnaires to 96 people in Bukit Tigo Village, Singkut District. The data analysis methods used in this research are instrument tests (validity and reliability tests), classical assumption tests (normality, multicollinearity and heteroscedasticity tests) and multiple linear regression analysis and statistical tests (t test, F test and coefficient of determination R2) . The results of this research show that knowledge has a positive and significant effect on interest in becoming a customer which can be determined using the t test with a significance value of 0.0039 < 0.05 and a tcount > ttable value of 2.092 > 1.98580. Perception of Profit Sharing has a positive and significant effect on interest in becoming a customer as evidenced by the significance value of 0.019 < 0.05 and the value and value of tcount > ttable, namely 2.397 > 1.98580. Simultaneously, knowledge and perception have a positive and significant effect on interest in becoming a public customer at Sharia Bank which can be seen from the F test, namely fcount > ftable or 5,329 > 3.09 and the resulting significance value is 0.006 < 0.005. The determinant coefficient value is 0.103 or 10.3% and the remaining 0.897 or 89.7% can be explained by other variables outside this research.